ACHIEVING UN-SDG 13 IN NIGERIA: ROLES OF RELIGIOUS LEADERS IN ADDRESSING CLIMATE CHANGE CHALLENGES - Abdussalam, Auwal F.; Abukur, Abba A. (FUDMA JOURNAL OF SCIENCES, 2021)
Religious leaders have major roles to play in enabling the world’s societies to take necessary actions to address climate change causes, impacts, and related issues effectively and ethically. This study investigates the roles they can play in achieving the United Nations Sustainable Development Goal 13 (Climate Action) in Nigeria. The study adopted a descriptive survey research design, it involved 300 participants; 150 religious leaders each from the Muslim and Christian communities in the three geopolitical zones of northern Nigeria (northwest, northeast and north-central). A structured questionnaire was used in collecting information from these leaders. Simple descriptive and One-way Analysis of Variance (ANOVA) statistics were used in analyzing the obtained data. Findings reveal that religious leaders (Muslims and Christians) do not differ in their perception about the causes of climate change in Nigeria (F = 2.37, p = <0.05); and as well do not differ in their perception of its impact (F = 1.54, p = <0.01). Although almost all (94%) of the religious leaders involved in this study strongly agree that they have an important role to play in achieving the UN-SDG 13 target, they however varied in agreeing to pressure the government on exploring an all-inclusive solution (F = 19.56, p = >0.05). The study also reveals that 21% of the respondents have already started some work in addressing climate change, 75% show strong interest in commencing activities in the areas of awareness, formulating community-based adaptation strategies, and engaging policymakers